2004
DOI: 10.1023/b:jaco.0000048517.19053.ff
|View full text |Cite
|
Sign up to set email alerts
|

A Hopf Operad of Forests of Binary Trees and Related Finite-Dimensional Algebras

Frédéric Chapoton

Abstract: Abstract. The structure of a Hopf operad is defined on the vector spaces spanned by forests of leaf-labeled, rooted, binary trees. An explicit formula for the coproduct and its dual product is given, using a poset on forests.Keywords: Hopf operad, binary tree, poset IntroductionThe theme of this paper is the algebraic combinatorics of leaf-labeled rooted binary trees and forests of such trees. We shall endow these objects with several algebraic structures.The main structure is an operad, called the Bessel oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Besides, the parts of the bigraded dimensions corresponding to the Poisson and Bessel suboperads are correct, i.e. match the well-known dimensions of Poisson and the dimensions of Bessel computed in [2].…”
Section: Propositionsupporting
confidence: 64%
See 2 more Smart Citations
“…Besides, the parts of the bigraded dimensions corresponding to the Poisson and Bessel suboperads are correct, i.e. match the well-known dimensions of Poisson and the dimensions of Bessel computed in [2].…”
Section: Propositionsupporting
confidence: 64%
“…This relation was already proposed for the Bessel suboperad in [2]. The algebras underlying R are given by generators and relations which have some resemblance with the Arnold relations and seem to contain the relations satisfied by some simple differential forms.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Note that the last eight terms in Eq. (5) are precisely corresponding to the eight kinds of admissible cuts in Adm(T ). Thus…”
Section: 2mentioning
confidence: 99%
“…Later, Brouder and Frabetti [3] showed that there exists a noncommutative Hopf algebra on planar binary trees which represents the renormalization group of quantum electrodynamics, and the coaction which describes the renormalization procedure. In the algebraic framework of Chapoton [5] for Bessel operad, a Hopf operad is constructed on the vector spaces spanned by forests of leaf-labeled binary rooted trees. Aguiar and Sottile further studied the structure of the Loday-Ronco Hopf algebra by a new basis in [1], where the product, coproduct and antipode in terms of this basis were also given.…”
Section: Introductionmentioning
confidence: 99%